Glial remodeling and choroidal vascular pathology in eyes from two donors with Choroideremia - Edwards, Malia M.; McLeod, D. Scott; Grebe, Rhonda; Bhutto, Imran A.; Dahake, Richa; Crumley, Kelly; Lutty, Gerard A. (Frontiers in Ophthalmology, 2022)
Choroideremia (CHM) is a recessive, X-linked disease that affects 1 in 50,000 people worldwide. CHM causes night blindness in teenage years with vision loss progressing over the next two to three decades. While CHM is known to cause progressive loss of retinal pigment epithelial (RPE) cells, photoreceptors and choroidal vessels, little attention has been given to retinal glial changes in eyes with CHM. In addition, while choroidal loss has been observed clinically, no histopathologic assessment of choroidal loss has been done. We investigated glial remodeling and activation as well as choriocapillaris changes and their association with RPE loss in postmortem eyes from two donors with CHM. Eyes were fixed and cryopreserved or the retina and choroid/RPE were processed as flatmounts with a small piece cut for transmission electron microscopy. A dense glial membrane, made up of vimentin and GFAP double-positive cells, occupied the subretinal space in the area of RPE and photoreceptor loss of both eyes. The membranes did not extend into the far periphery, where RPE and photoreceptors were viable. A glial membrane was also found on the vitreoretinal surface. Transmission electron microscopy analysis demonstrated prominence and disorganization of glial cells, which contained exosome-like vesicles. UEA lectin demonstrated complete absence of choriocapillaris in areas with RPE loss while some large choroidal vessels remained viable. In the far periphery, where the RPE monolayer was intact, choriocapillaris appeared normal. The extensive glial remodeling present in eyes with CHM should be considered when therapies such as stem cell replacement are considered as it could impede cells entering the retina. This gliosis would also need to be reversed to some extent for Müller cells to perform their normal homeostatic functions in the retina. Future studies investigating donor eyes as well as clinical imaging from carriers or those with earlier stages of CHM will prove valuable in understanding the glial changes, which could affect disease progression if they occur early. This would also provide insights into the progression of disease in the photoreceptor/RPE/choriocapillaris complex, which is crucial for identifying new treatments and finding the windows for treatment.